2023
DOI: 10.1177/21650799231164783
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Elastomeric Half Mask Respirator Knowledge and User Barriers on Safety Climate Perceptions in Health Care Settings

Abstract: Background: Availability of personal protective equipment (PPE) and its effective use may influence safety climate perceptions among health care personnel (HCP). It is unclear how health care organizations can leverage the effective use of respiratory protection to engage in continuous improvement of their safety climate, which can inform opportunities for employee education and engagement. Methods: After using an elastomeric half mask respirator (EHMR) as their primary form of respiratory protection for sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A previous study by the same authors found the need to develop and maintain RPPs, among other initiatives, to not only positively influence safety climate perceptions, but also support participation in consistent PPE practices among HCP. 49 Specifically, management oversight and organizational support and dissemination of the RPP has been positively correlated with health employees' perceptions regarding how their employer prioritizes health and safety. 50 Further, a deployment of EHMRs within an ambulatory setting during the COVID-19 pandemic suggested the importance of updating and having an RPP in place before the rollout of new EHMRs to support employee adherence to required PPE use and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by the same authors found the need to develop and maintain RPPs, among other initiatives, to not only positively influence safety climate perceptions, but also support participation in consistent PPE practices among HCP. 49 Specifically, management oversight and organizational support and dissemination of the RPP has been positively correlated with health employees' perceptions regarding how their employer prioritizes health and safety. 50 Further, a deployment of EHMRs within an ambulatory setting during the COVID-19 pandemic suggested the importance of updating and having an RPP in place before the rollout of new EHMRs to support employee adherence to required PPE use and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore specific training and communication practices that have been successfully deployed by organizational leadership to support aspects of a positive safety climate. For example, previous research has shown the value of fostering a respirator champion program to en-courage the use of EHMRs through peer-to-peer support and interaction [2,44]. It is likely that these holistic approaches to respirator management-that foster a positive culture around respirator use-will be critical as new types of respirators enter the market.…”
Section: The Role Of Safety Climatementioning
confidence: 99%